S-D Logic and CSR: the management of social capital for the value creation in SMEs - Alessandra De Chiara (jbm - Journal of Business Market Management, 2012)
This paper underlines the importance of relationships with stakeholders for co-create value, according to Service Dominant Logic and Corporate Social Responsibility approaches, and the importance of the management of social capital, in order to strengthen the relational nature of firms. Focusing on SME's, the management of social capital and of reputation and trust, all assets of social capital, is at the base of the long-term performance of SME's. Their ability to create consent and to develop trust around the entrepreneurial project is an essential element for such enterprises and the management of social capital, in a 'responsible' view, appears to be a strategic aspect.
urn:nbn:de:0114-jbm-v5i2.176
Keywords: 650; Corporate Social Responsibility; S-D Logic; SMEs; Social capital; Corporate Social Responsibility; Service-dominant logic; Social Capital; Betriebliche Wertschöpfung; KMU